Cognitive function restoration in rats with chronic brain ischemia using Semax and hopantenic acid comprehensive administration - Kirchev, V. (Journal of Education, Health and Sport, 2023)
The relevance and importance of treating patients with ischemic brain lesions are indisputable. Chronic ischemic processes in the brain occur much more frequently than acute cerebral circulation disorders, leading to prolonged disability and being the main contributors to a significant number of strokes. Cognitive dysfunctions prevail in the dynamics of the post-ischemic period and are often the primary determinants of the severity of residual organic and subsequent functional impairments of the brain. The aim of the study is to investigate the effectiveness of separate and combined administration of Semax and hopantenic acid in the pharmacological correction of cognitive disorders in rats with experimental chronic brain ischemia. It has been established that rats with chronic brain ischemia exhibit cognitive impairments from the 1st day, manifested in worsened learning processes, short-term and long-term memory functioning in the context of conditioned active avoidance and conditioned feeding reflexes. It has been shown that separate and combined application of Semax and hopantenic acid contributes to the restoration of the learning process and improvement of mnestic functions in rats with chronic brain ischemia. The most pronounced nootropic effect in rats with chronic brain ischemia was registered under the conditions of combined administration of Semax and hopantenic acid, starting from the 3rd day of the study. Subsequently, in terms of anti-ischemic efficacy, the effect of Semax follows, which was realized starting from the 3rd day of the study. The least pronounced neuroprotective effect belongs to hopantenic acid, starting from the 7th day of the study. The author considers the obtained data as experimental groundwork for the feasibility of clinically testing the nootropic effects of the combined administration of Semax and hopantenic acid in cases of chronic brain ischemia. The comprehensive pharmacological correction of cognitive disorders in chronic brain ischemia is pathogenetically justified and aimed at activating sanogenetic mechanisms.